(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the compliance with the surgical safety checklist among medical staff and to identify related factors at Nghe An General Friendship Hospital in 2025. Methods: A cross-sectional descriptive study with analytical components was conducted on 300 type-I surgical procedures performed at the Department of Anesthesiology and Resuscitation from January to June 2025. Each surgical procedure involved six members of the surgical team, generating 1,800 observations of compliance behaviors. The primary outcome was full compliance with the surgical safety checklist at three critical points: before anesthesia induction, before skin incision, and before the patient leaves the operating room. Because multiple observations were nested within the same surgical procedure, logistic regression models with cluster-robust standard errors adjusted for surgical cases were used to account for intra-cluster correlation. Results: The overall compliance rate with the surgical safety checklist was 91.3%. Surgeons, anesthesiologists, and nurses demonstrated high compliance levels (>92%) across most checklist items. Factors significantly associated with compliance included years of professional experience, possession of surgical safety certification, annual training on surgical safety, supervision by the infection control unit, and the presence of standardized surgical safety protocols within the hospital (p < 0.05). Conclusion: Compliance with the surgical safety checklist at Nghe An General Friendship Hospital was high; however, the final stage before the patient leaves the operating room showed comparatively lower adherence. Continuous training, strengthened supervision, and reinforcement of patient safety culture are necessary to further improve compliance within surgical teams.